The Effect of Traditional Games on Students Physical Fitness Levels - Irwanto, Dhanil; Septianingrum, Kartika; Utomo, Andy Widya Bayu (Newinera Publisher, 2025)
This study aims to determine the effect of traditional games on the level of physical fitness of students at SMK Terpadu Jannatul Firdaus, Ngawi Regency. The study used a quantitative approach with a quasi-experimental design method of non-randomized control group pretest-posttest design. The sample consisted of 40 students of grades X and XI who were divided into an experimental group (using the gobak sodor game) and a control group (regular physical exercise). Data were collected through the Nusantara Student Fitness Test (TKPN) and analyzed using a paired sample t-test. The results showed that there was a significant difference between the pretest and posttest scores in the experimental group (p <0.05), which indicated that traditional games had a positive effect on improving students' physical fitness. This finding confirms that the integration of traditional games in physical education learning can be an effective and enjoyable alternative to improve students' physical fitness.